1986
DOI: 10.1159/000199384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short- and Long-Term Feeding of Omeprazole on Rat Gastric Endocrine Cells

Abstract: Rats were tube-fed with omeprazole (40 μmol/kg body weight twice daily) for 30 and 60 days. As a result, fasting plasma gastrin levels were significantly elevated, while plasma somatostatin levels remained normal. Gastrin concentrations in the antral mucosa were unchanged after 30 days, but significantly elevated after 60 days. The relative stomach weight and the area of the antral and oxyntic mucosa increased significantly; however, the oxyntic mucosa thickness and the volume density of the parietal cells did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 0 publications
3
28
1
2
Order By: Relevance
“…The increase in antral mucosal height was observed after only 1 month of treatment (+480/0) but was not significant (P=O-lO, n = 4), while at that time no evident increase in fundic mucosal height was noted between control and Om groups (data not shown). This is in keeping with previous published results [22] but is at variance with others 1171. It is well known that gastrin exerts a trophic effect on fundic mucosa [24-261, however discrepancies exist concerning its action on antral mucosa [9, 24,27].…”
Section: Discussionsupporting
confidence: 94%
“…The increase in antral mucosal height was observed after only 1 month of treatment (+480/0) but was not significant (P=O-lO, n = 4), while at that time no evident increase in fundic mucosal height was noted between control and Om groups (data not shown). This is in keeping with previous published results [22] but is at variance with others 1171. It is well known that gastrin exerts a trophic effect on fundic mucosa [24-261, however discrepancies exist concerning its action on antral mucosa [9, 24,27].…”
Section: Discussionsupporting
confidence: 94%
“…Here the volume density increased from 0.73 ± 0.1 to 0.86 ± 0.09. This increase was not significant and is much smaller than that observed in rats after 8 weeks of treatment with 14 mg/kg omepra zole daily [ 16], and were far below the values estimated in 8 patients with gastrinoma (1.37 ± 0.22%). No clusters of endocrine cells were found.…”
Section: Pathogenesis Of Endocrine Cell Proliferationcontrasting
confidence: 67%
“…Chronic application of acidinhibitory drugs elevates serum gastrin levels (14,16,30), and it has been suggested that the gastric pH influences the population of endocrine cells such as gastrinproducing G cells (30)(31)(32). The long-term elevation of gastric pH may increase G-cell density and then elevate serum gastrin levels.…”
Section: Discussionmentioning
confidence: 99%